Synthesis of 3-Iodoquinolines by Copper-Catalyzed Tandem Annulation from Diaryliodoniums, Nitriles, and 1-Iodoalkynes - Wang, Xuesong; Wang, Xingyong; Huang, Dayun; Liu, Chulong; Wang, Xinyan; Hu, Yuefei (Advanced synthesis & catalysis, 2016)
A novel method for the synthesis of 3‐iodoquinolines was developed by copper‐catalyzed tandem annulation from diaryliodoniums, nitriles, and 1‐iodoalkynes. It is a method that is characterized by the most convenient operation and wide molecular diversity.